Akurasi Model Logistik Springate, Zmijewski, dan Grover Dalam Menakar Kesulitan Keuangan Perusahaan Pembiayaan - Munawarah, Munawarah (JURNAL AKUNTANSI DAN MANAJEMEN, 2019)
This study aims to determine springate, grover and zmijewski able to predict the condition of financial distress in finance companies listed on the Indonesia Stock Exchange. From  three models can be known which model is the most accurate in predicting financial distress. There are 17 companies in Financing sector as population in this study from 2013-2017. Using purposive sampling technique, total sample of 85 financing companies was obtained. Secondary data were used in this research sourced from the company's annual reports. The analysis model used is logistic regression. Simultaneously, all predictive models affect the probability of financial distress. While partially only Zmijewski can influence the prediction of financial distress conditions in Financing sub-sector companies listed on the Indonesia Stock Exchange. Nagelkerqe Square value shows 0.606 meaning that only 60.6% variation of the accuracy of these three models in predicting financial distress conditions of finance companies. While 39.4% can be explained by other models not examined in this study.